Israeli perspectives on the Palestinian refugee issue - Gal, Orit (2008)
At the beginning of the Oslo Process the greatest challenge was the question of Palestinian statehood; negotiation of the refugee issue was postponed until the later stages. Over a decade later, Palestinian statehood is generally accepted as a given, and the refugee issue has taken centre stage. The Israeli perspective, from a leadership standpoint, is seemingly characterized by a sense of being overwhelmed, owing to the complexity of elements making up the refugee issue, the multiplicity of actors involved, and a heightened sense of uncertainty as to the consequences of any negotiated settlement. More strategic work is needed at the political and policy-making level to determine the resolution level required for the agreement itself. Much of the detail involved will have to be developed outside the main negotiation framework. More research and strategy development work is needed concerning the Israeli public domain, to assess existing attitudes and possible avenues for widening the public discourse. To this end, the Israeli media should also be encouraged to present the different debates and elements of the issue. There is a need for an international task force of leading experts working alongside the negotiation process and translating both sides' strategic options into operational frameworks. Such support could ease the load on the actual negotiating parties, thereby facilitating the decision-making process.